CRIMINAL RESPONSIBILITY FOR FINES TO CORPORATIONS IN CRIMINAL ACTS OF CORRUPTION BASED ON EMPLOYMENT RELATIONSHIPS - Oesman, Rusdi; Haryono, Waty Suwarty; Hartanto (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
This study aims to determine the criminal liability of corporations in corruption crimes and to determine the application of material criminal law in Decision Number 1751 / Pid.Sus / 2020 / PT Mdn., and Decision Number 47 / Pid.Sus-TPK / 2022 / PT Dki. The research method used is normative legal research, by using the Statute Approach and Case Approach methods . This study uses a type of normative legal research with a statute approach and a case approach. The sources of legal materials used are primary and secondary legal materials. The method used by the author is the library method, then the analysis of the legal materials used is descriptive of the legal materials obtained. The results obtained from this study are: 1). The qualification of the Criminal Act of Deleting Account Records of a Bank is regulated in Article 49 paragraph (1) letter c of the Banking Law which stipulates that Members of the Board of Commissioners, Directors, or Bank Employees who intentionally change, obscure, hide, delete, or eliminate any records in the books or in reports, or in documents or reports of business activities, transaction reports or accounts of a bank, or intentionally change, obscure, eliminate, hide or damage the bookkeeping records, shall be subject to imprisonment of at least five years and a maximum of fifteen years and a fine of at least ten billion rupiah and a maximum of two hundred billion rupiah, and 2). The panel of judges who examined and decided on Case Decision Number 1751/Pid.Sus/2020/PT Mdn., and Decision Number 47/Pid.Sus-TPK/2022/PT Dki. The author believes that the panel of judges has examined and tried this case properly, considering the public prosecutor's indictment, demands, defense from the defendant and his legal counsel, evidence, and other facts revealed at the trial.